Respuesta :
Answer:
k = -2
Step-by-step explanation:
83=4k-7(1+7k)
Distribute
83=4k-7-49k
Combine like terms
83 = -45k -7
Add 7 to each side
83+7 = -45k-7+7
90 = -45k
Divide each side by -45
90/-45 = -45k/-45
-2 = k
Answer:
k = -2
Step-by-step explanation:
Step 1: Use 7 to open the bracket :
-7(1+7k)=-7-49k
Step 2: Collect like terms
Step 3 : Divide both sides of the equation by -45
[tex]83=4k-7(1+7k) \\ \\83 = 4k-7-49k\\\\ 83+7=4k-49k\\\\90 = -45k\\\\\frac{90}{-45} = \frac{-45k}{-45} \\\\k = -2[/tex]